1995
DOI: 10.1074/jbc.270.20.11921
|View full text |Cite
|
Sign up to set email alerts
|

Cross-reactivity of Antibodies to Retro-Inverso Peptidomimetics with the Parent Protein Histone H3 and Chromatin Core Particle

Abstract: A series of monoclonal antibodies has been generated against an hexapeptide of sequence IRGERA corresponding to the C-terminal residues 130-135 of histone H3 and three analogues of this model peptide. The analogues correspond to the D-enatiomer, containing only D-residues, and two retro-peptides containing NH-CO bonds instead of natural amide peptide bonds. The chirality of each residue was maintained in the retro-peptide and inverted in the retro-inverso-peptide. Monoclonal antibodies were generated from mice… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
68
0

Year Published

1998
1998
2009
2009

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 62 publications
(73 citation statements)
references
References 17 publications
5
68
0
Order By: Relevance
“…In contrast with these results, we have recently described the generation in mice of antibodies against an all-Dhexapeptide of sequence IRGERA corresponding to the COOH-terminal residues 130-135 of histone H3 (9). Antibodies of the IgG3 isotype induced against either the D-or L-peptide were able to bind both the homologous peptide and its mirror enantiomer.…”
mentioning
confidence: 63%
See 3 more Smart Citations
“…In contrast with these results, we have recently described the generation in mice of antibodies against an all-Dhexapeptide of sequence IRGERA corresponding to the COOH-terminal residues 130-135 of histone H3 (9). Antibodies of the IgG3 isotype induced against either the D-or L-peptide were able to bind both the homologous peptide and its mirror enantiomer.…”
mentioning
confidence: 63%
“…Three analogues of the model peptide of sequence IRGERA corresponding to the COOH-terminal residues 130-135 of histone H3 were produced. Preparation and purification of L-and all-D IRGERA peptides have been described (9). The two new analogues, the retro-inverso-and retro-peptides, were synthesized as the L-and D-peptides by the solid-phase methodology in Boc chemistry on a p-methylbenzhydrylamine resin (Applied Biosystems) (11).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, antibodies to the parent peptide and its RI isomer cross-reacted strongly with human histone H3 and with chromatin units containing histone H3. 40 Indeed, Briand and coworkers reported that end-group RI analogs of histone H3[130 -135] were strongly recognized by autoantibodies from lupus mice and from sera of patients with rheumatoid arthritis, diseases characterized by inflammatory reactions associated with increased levels of proteolytic enzymes. 41 These findings strongly suggest a potential role for RI peptides as antigens in immunodiagnostic assays.…”
Section: Ri Peptides As Immunogens Immunomodulators and Diagnostic mentioning
confidence: 99%